2022
DOI: 10.1101/2022.02.02.478874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational transitions of the mitotic adaptor Spindly underlie its interaction with Dynein and Dynactin

Abstract: Cytoplasmic Dynein 1, or Dynein, is a microtubule minus-end directed motor. Dynein motility requires Dynactin and a family of activating adaptors that stabilize the Dynein-Dynactin complex and promote regulated interactions with cargo in space and time. How activating adaptors limit Dynein activation to specialized subcellular locales is unclear. Here, we reveal that Spindly, a mitotic Dynein adaptor at the kinetochore corona, exists natively in a closed conformation that occludes binding of Dynein-Dynactin to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 105 publications
2
6
0
Order By: Relevance
“…The resulting prediction shows high confidence for the Spindly motif interacting with site 4 as well as a preceding break in the coiled-coil, consistent with the density. Interestingly, other cargo adaptors may also have coiled-coil breaks preceding their Spindly motifs (Figure S8C), as recently predicted [d’Amico et al, 2022]. Our structure now shows that the highly conserved Spindly motif residue Leu347 sits in a hydrophobic pocket at the edge of p25 (Figure 6B).…”
Section: Resultssupporting
confidence: 84%
“…The resulting prediction shows high confidence for the Spindly motif interacting with site 4 as well as a preceding break in the coiled-coil, consistent with the density. Interestingly, other cargo adaptors may also have coiled-coil breaks preceding their Spindly motifs (Figure S8C), as recently predicted [d’Amico et al, 2022]. Our structure now shows that the highly conserved Spindly motif residue Leu347 sits in a hydrophobic pocket at the edge of p25 (Figure 6B).…”
Section: Resultssupporting
confidence: 84%
“…As kinetochores enrich MPS1 during mitosis, and MPS1 activity is highest at these structures, albeit not limited to them (Kuijt et al , 2020), polymerization may become naturally spatially limited to kinetochores. The release of ROD from an auto‐inhibited state upon MPS1 phosphorylation, postulated here, should be considered alongside the proposed auto‐inhibition of Spindly, shown to involve an intramolecular interaction of its coiled coils (Sacristan et al , 2018; preprint: d’Amico et al , 2022). It is remarkable that sequence determinants in the CC2 of Spindly, when deleted (Spindly ∆276‐306 ), not only prevent the intramolecular interaction with CC1a/b, filamentation in vitro , and ectopic filament formation (Sacristan et al , 2018; preprint: d’Amico et al , 2022), but also kinetochore recruitment.…”
Section: Discussionmentioning
confidence: 80%
“…The release of ROD from an auto‐inhibited state upon MPS1 phosphorylation, postulated here, should be considered alongside the proposed auto‐inhibition of Spindly, shown to involve an intramolecular interaction of its coiled coils (Sacristan et al , 2018; preprint: d’Amico et al , 2022). It is remarkable that sequence determinants in the CC2 of Spindly, when deleted (Spindly ∆276‐306 ), not only prevent the intramolecular interaction with CC1a/b, filamentation in vitro , and ectopic filament formation (Sacristan et al , 2018; preprint: d’Amico et al , 2022), but also kinetochore recruitment. In a previous study, a deletion of residues 254–284 of Spindly was shown to retain kinetochore localization, whereas a deletion of the first 292 residues impaired kinetochore localization (Barisic et al , 2010).…”
Section: Discussionmentioning
confidence: 80%
“…The C-terminal end of the coiled coil contacts the dynactin pointed end complex (Urnavicius et al 2015). A conserved Spindly-box motif (Gama et al 2017), frequently separated from the coiled-coil by a loop (Chaaban and Carter 2022, d’Amico et al 2022), plays a key role in this interaction (Lau et al 2021, Chaaban and Carter 2022). Further, a dynein heavy chain binding site motif (HBS1 or previously the CC2 box) is present between the DLIC binding site and the Spindly box (Sacristan et al 2018, Chaaban and Carter 2022).…”
Section: Introductionmentioning
confidence: 99%